I Know I Can, but Do I Have the Time? The Role of Teachers’ Self-Efficacy and Perceived Time Constraints in Implementing Cognitive-Activation Strategies in Science - Teig, Nani; Scherer, Ronny; Nilsen, Trude (Frontiers in Psychology, 2019)
Considerable research has demonstrated that teachers’ self-efficacy plays a major role in implementing instructional practices in classroom lessons. Only few studies, however, have examined the interplay between how teachers’ self-efficacy and the challenges that lie outside their influence are related to their implementation of cognitive-activation strategies (CAS), especially in science classrooms. Using the Trends in Mathematics and Science Study (TIMSS) 2015 data from Grades 4, 5, 8, and 9, we explored the extent to which teachers’ self-efficacy in teaching science and the perceived time constraints explained variation in the enactment of general and inquiry-based CAS. Overall, the findings revealed that highly self-efficacious teachers reported more frequent implementation of both general and inquiry-based CAS, whereas those who perceived strong time constraints reported a less frequent use of inquiry-based CAS. We further found that these relations differed significantly between primary- and secondary-school teachers and discuss these findings in light of teachers’ professional competences and the resources for science activities in primary and secondary education. We point to the theoretical implications of this study for enhancing the conceptual understanding of generic and specific aspects of CAS and the practical implications for teacher education, professional development, and educational policy.